Rhodamine-based conjugated polymers: potentiometric, colorimetric and voltammetric sensing of mercury ions in aqueous medium. Issue 18 (21st August 2017) - Ayranci, Rukiye; Demirkol, Dilek Odaci; Timur, Suna; Ak, Metin
Abstract : Herein, we report the synthesis and characterization of a conducting polymer film used as a simple and novel multi-signal sensor platform which demonstrates ion selective potentiometric, colorimetric and voltammetric responses in aqueous media. Abstract : Herein, we report the synthesis and characterization of a new rhodamine-based monomer (RD-CZ), and an investigation of the optical and electrochemical properties of the corresponding polymer (P(RD-CZ)), which was electropolymerized on an ITO electrode. The resulting P(RD-CZ) polymer film was used as a simple and novel multi-signal sensor platform, which demonstrates ion-selective potentiometric, colorimetric and voltammetric responses in aqueous media for the first time. P(RD-CZ) exhibits excellent selectivity for Hg 2+ ions compared with Cd 2+, Cu 2+ Zn 2+, and Fe 3+ using the potentiometric technique, which depends on the increasing charge carrier transport through rhodamine-bound Hg 2+ with a limit of detection (LOD) of 9.77 × 10 −8 M. The P(RD-CZ) polymer film also exhibits a distinct color change from orange to purple, which is detectable even by the naked eye, in the presence of Hg 2+ ions. The LOD for Hg 2+ ions obtained using the colorimetric method is 3.16 × 10 −8 M. The same material has also been used for the voltammetric sensing of Hg 2+ in aqueous media with a detection limit of 1 × 10 −7 M. In this study, a conductive polymer-based sensor platform for detecting mercury ions via three different methods has been designed for the first time. By doing so, a disposable planar paper-based ion-sensing platform, which is suitable for low-cost point-of-care and in-field testing applications, could be fabricated with a highly reproducible and linear response towards different concentrations of analyte ions in aqueous and biological samples.